054 Impact of online adult headache guideline on headache referral to neurology clinic. (29th July 2019) - Huang, Leon; Bourke, David; Ranta, Anna
Abstract : Introduction: Headache is a common problem in primary care and is one of the main reasons for general practitioners to consult neurology service. Decision for referral may be influenced by uncertainty of diagnosis and referrer's clinical confidence in identifying risks of secondary causes. We examined the effect of an online guideline for adult headache on referrals to neurology service, and analyse the quality of the referrals and outcome of their clinical assessment. Methods: We examined the referrals in selected months within 2 years before and 2 years after online publication of a headache guideline developed by our neurology department. Referrals for headaches being the primary complaint were analysed. The primary outcome was the proportion of neurology referrals for headache as the primary complaint pre- versus post guideline. Results: Nine hundred neurology referrals before and 801 neurology referrals after the publication of online headache guideline were included. There was a significant reduction in proportion of neurology referrals for headaches (OR = 0.73 (0.55 – 0.96), p = 0.026). The proportion of headache referrals requiring face-to-face assessment in clinic was also reduced from 69% before and 53% after publication of the headache guideline (p=0.014). There are similar proportions of patient referred without adequate trial of preventative medication prior (33.8% vs. 27.7%), and over used analgesics (21.9% vs. 25.0%). Conclusions: The headache guideline demonstrated effectiveness in reducing demand for assessment of headaches in neurology clinic. Headache management prior to referral is an ongoing area of concern.